2020
DOI: 10.1029/2019ef001435
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in the Annual Range of Precipitation Under Stabilized 1.5°C and 2.0°C Warming Futures

Abstract: Changes in hydrological cycle under 1.5°C and 2.0°C warming are of great concern on the post-Paris Agreement agenda. In particular, the annual range of precipitation, that is, the difference between the wet and dry seasons, is important to society and ecosystem. This study examines the changes in precipitation annual range using the Community Earth System Model low-warming (CESM-LW) experiment, designed to assess climate change at stabilized 1.5°C and 2.0°C warming levels. To reflect the exact annual range in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
(107 reference statements)
1
15
0
Order By: Relevance
“…There are also a few recent studies reported in the literature (Lee et al, 2018;Chen et al, 2018;Li et al, 2019;Chen et al, 2020) to assess changes of the East Asian summer monsoon system in the stabilized 1.5°C and 2°C warmer worlds. Although results from the stabilized and transient scenarios are qualitatively consistent in projecting an increased frequency and intensity of extreme precipitation over East Asia, there exist significant differences in the response of summer monsoon and in the spatial…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…There are also a few recent studies reported in the literature (Lee et al, 2018;Chen et al, 2018;Li et al, 2019;Chen et al, 2020) to assess changes of the East Asian summer monsoon system in the stabilized 1.5°C and 2°C warmer worlds. Although results from the stabilized and transient scenarios are qualitatively consistent in projecting an increased frequency and intensity of extreme precipitation over East Asia, there exist significant differences in the response of summer monsoon and in the spatial…”
Section: Accepted Articlementioning
confidence: 99%
“…There are also a few recent studies reported in the literature (L. Chen et al, 2018, Z. Chen et al, 2020Lee et al, 2018;D. Li et al, 2019) to assess changes of the East Asian summer monsoon system in the stabilized 1.5°C and 2°C warmer worlds.…”
mentioning
confidence: 99%
“…The experimental outputs from the CMIP6 models contain more sophisticated and modified parameterization schemes for dynamic processes and have designed new emission scenarios for the projections (O'Neill et al ., 2014; Kawai et al ., 2019; Park et al ., 2019; Gusain et al ., 2020). Efforts on the assessments and future projection of climate extremes have been implemented recently by using CMIP6 models (Jiang et al ., 2020; Chen et al ., 2020a, 2020b, 2020c, 2020d). Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing interest in measuring the regional responses to climate change to understand how these may vary for different levels of global warming. Prior research has shown that both observed and projected changes in surface temperatures and precipitation exhibit large regional variations, and spatial features of precipitation changes are even more regionally variable than changes in temperature (Adler & Gu, 2015; Chen et al., 2020; Contractor et al., 2020; Dunn et al., 2020; Feng et al., 2014; Gao et al., 2020). To facilitate decision‐making on mitigation and adaptation strategies and formulate warming targets to avoid unacceptable climate change, it is necessary to understand and quantify potential spatial heterogeneity in the climate change response.…”
Section: Introductionmentioning
confidence: 99%